Rare dystopias - Queirolo Maglio, Guillermo (2015)
Four different types of rare Dystopias are studied. Two cases of chronic uterine inversion occur, Spinelli exposing technique that was used in one of them. Thirteen cases of vaginal vault prolapse Vaginal prolapse and three cervical stump, are presented exposing the vaginal technique.